Safety Evaluation of Bifidobacterium lactis BL-99 and Lacticaseibacillus paracasei K56 and ET-22 in vitro and in vivo - Lu, Hongyun; Zhao, Wen; Liu, Wei-Hsien; Sun, Ting; Lou, Hanghang; Wei, Tianyu; Hung, Wei-Lian; Chen, Qihe (Frontiers in Microbiology, 2021)
Probiotics have been reported to play a major role in maintaining the balance of microbiota in host. Consumption of food with probiotics has increased with consumer concerns regarding healthy diets and wellness. Correspondingly, safety evaluation of probiotics for human consumption has become increasingly important in food industry. Herein, we aimed to test the safety of Bifidobacterium lactis BL-99 and Lacticaseibacillus paracasei K56 and ET-22 strains in vitro and in vivo. In results, these strains were found to be negative for mucin degradation and platelet aggregation test. Additionally, the three strains were susceptible to eight antibiotics. In accordance with bacterial reversion mutation (Ames) assay, the tested strains had no genetic mutagenicity. Finally, it was confirmed that there were no dose-dependent mortality and toxicity throughout multidose oral toxicity tests in rats. Our findings demonstrated that B. lactis BL-99 and L. paracasei K56 and ET-22 can achieve the generally recognized as safe (GRAS) status as probiotics in the future.